Moisture Localization and Diagnosis Method for Power Distribution Cables Based on Dynamic Frequency Domain Reflectometry - Hongzhou Zhang; Kai Zhou; Xiang Ren; Yefei Xu (Energies)
Moisture ingress in power distribution cable bodies can lead to insulation degradation, jeopardizing the operational safety of power grids. However, current cable maintenance technologies lack effective diagnostic methods for identifying moisture defects in cable bodies. To address this gap, this paper proposes a dynamic frequency domain reflectometry (D-FDR) method for moisture localization and diagnosis in power distribution cables. Leveraging the temperature-sensitive nature of moisture defects—in contrast to the temperature-insensitive characteristics of other defects—the method involves the application of thermal excitation to induce differential dynamic changes in the distributed capacitance of moisture-affected cable segments compared to normal segments, enabling the precise identification and diagnosis of moisture ingress. Simulations and experiments confirm that moisture ingress in cable bodies increases the distributed capacitance, generating reflection peaks at corresponding distances on frequency domain localization plots. Under thermal excitation, the reflection peak amplitude of moisture defects exhibits a temperature-dependent decrease, distinct from the behavior of intact cables (amplitude increase) and copper shielding layer damage (negligible variation). By utilizing the dynamic characteristics of reflection peak amplitudes as diagnostic criteria, this method is able to accurately localize and diagnose moisture defects in cable bodies.